Characterization of micromixing in T-jet mixers - Krupa, K.
To assess micromixing in T-jet mixers, having various geometries and flow rates, a set of test reactions was employed. This consisted of the reactions between 1-naphthol/2-naphthol and diazotized sulfanilic acid in aqueous solution. The results showed that the Reynolds number has a large effect on the rate of mixing. Furthermore, the geometrical parameters also influenced the product distribution of the test reactions. Increasing the ratio between the mixing chamber width and the inlet jet width improved mixing. Shallow chambers can show poorer mixing while increasing the depth enhances both mixing and reactor capacity. A characteristic mixing time was defined and determined as a function of Reynolds number in the range 300-3000 for the various reactor geometries. The effects of chamber width and depth as well as of jet width on product distributions and mixing times were related to the flow regimes found earlier by Planar Laser Induced Fluorescence.